2021
DOI: 10.1002/ijc.33911
|View full text |Cite
|
Sign up to set email alerts
|

mdm2 gene amplification is associated with luminal breast cancer progression in humanized PDX mice and a worse outcome of estrogen receptor positive disease

Abstract: Estrogen receptor‐positive breast cancer is a highly prevalent but heterogeneous disease among women. Advanced molecular stratification is required to enable individually most efficient treatments based on relevant prognostic and predictive biomarkers. First objective of our study was the hypothesis‐driven discovery of biomarkers involved in tumor progression upon xenotransplantation of Luminal breast cancer into humanized mice. The second objective was the marker validation and correlation with the clinical o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
(123 reference statements)
1
3
0
Order By: Relevance
“…In the METABRIC cohort, the Kaplan-Meier survival curves revealed that samples with MDM2 CN amplification or those with CDKN2A CN deep deletion presented worse prognosis (Figure 7A and B). The results of the samples with MDM2 CN amplification were consistent with those in previous reports (28,29). However, there were no statistically significant differences in the median cut-off values of MDM2 and CDKN2A mRNA expression levels (Supplementary Figure S2A-D).…”
Section: Samples With Mdm2 Cn Amplification or Those Withsupporting
confidence: 90%
“…In the METABRIC cohort, the Kaplan-Meier survival curves revealed that samples with MDM2 CN amplification or those with CDKN2A CN deep deletion presented worse prognosis (Figure 7A and B). The results of the samples with MDM2 CN amplification were consistent with those in previous reports (28,29). However, there were no statistically significant differences in the median cut-off values of MDM2 and CDKN2A mRNA expression levels (Supplementary Figure S2A-D).…”
Section: Samples With Mdm2 Cn Amplification or Those Withsupporting
confidence: 90%
“…It may be involved in preneoplastic processes, as it is detected in benign breast tumors [ 74 ]. Xu et al [ 75 ] had reported that NUF2 is overexpressed in breast cancer and significantly connected to multiple pathological features and prognosis of breast cancer. MDM2 from Cluster 4 is a cancer-related gene that encodes a nucleus-localized E3 ubiquitin ligase; such protein can promote tumor formation by targeting tumor suppressor proteins, e.g., p53, for proteasomal degradation.…”
Section: Discussionmentioning
confidence: 99%
“…NOD.Cg-Prkdc scid Il2rg tm1Wjl /SzJ (NSG) mice were obtained from Jackson Laboratories and housed and bred in a specialized pathogen-free facility at the University of Regensburg. Humanized tumor mice were generated as previously described [36]. In brief, newborn animals were irradiated with 1 Gy during the first 48 h of life span.…”
Section: Generation Of Humanized Patient-derived Tumor Mice (Hpdx)mentioning
confidence: 99%